2017
DOI: 10.1186/s12913-017-2127-1
|View full text |Cite
|
Sign up to set email alerts
|

The effect of referral templates on out-patient quality of care in a hospital setting: a cluster randomized controlled trial

Abstract: BackgroundThe assessment of quality of care is an integral part of modern medicine. The referral represents the handing over of care from the general practitioner to the specialist. This study aimed to assess whether an improved referral could lead to improved quality of care.MethodsA cluster randomized trial with the general practitioner surgery as the clustering unit was performed. Fourteen surgeries in the area surrounding the University Hospital of North Norway Harstad were randomized stratified by town ve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 66 publications
0
8
0
Order By: Relevance
“…The authors conceded that the study lacked a solid analytical framework. A final analysis (Wahlberg et al ., 2017) investigated the impact of the referral template on the quality of care received in the hospital and, similarly, no significant improvement in hospital care was observed. A large number of assessors were involved in grading the quality of referrals, which may have implications for reproducibility of the findings.…”
Section: Resultsmentioning
confidence: 99%
“…The authors conceded that the study lacked a solid analytical framework. A final analysis (Wahlberg et al ., 2017) investigated the impact of the referral template on the quality of care received in the hospital and, similarly, no significant improvement in hospital care was observed. A large number of assessors were involved in grading the quality of referrals, which may have implications for reproducibility of the findings.…”
Section: Resultsmentioning
confidence: 99%
“…An intuitive first-step solution to address the quantity of low-quality referrals would be to develop and implement a mandatory standardized IBD referral form; however, we found that although a standard form was available, it was only used 7.5% of the time. Previous research also supports that standard forms are rarely used by referring providers ( 24 ). This study found that referring providers significantly influence patient wait time.…”
Section: Discussionmentioning
confidence: 67%
“…The present study provides new evidence regarding the value of clinical checklists, and to our knowledge, it is one of few studies assessing the impact of electronic checklists on the clinical assessment of referral letters [ 21 , 25 ]. Studies evaluating the impact of improved referral quality on patient outcomes are also scarce [ 25 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, no significant changes were detected in patient outcomes. Wahlberg et al [ 22 ] showed improved referral quality after implementing referral templates for dyspepsia, colorectal cancer, chest pain and chronic obstructive pulmonary disease, but were not able to show any impact on prioritization of the patients [ 29 ].…”
Section: Discussionmentioning
confidence: 99%